The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1101/424259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly Mutable Linker Regions Regulate HIV-1 Rev Function and Stability

Abstract: The HIV-1 protein Rev is an essential viral regulatory protein that facilitates the nuclear export of intron-containing viral mRNAs. Its sequence is organized into short, structured, functionally well-characterized motifs joined by less understood linker regions. We recently carried out a competitive deep mutational scanning study, which determined the relative fitness of every amino acid at every position of Rev in replicating viruses. This study confirmed many known constraints in Rev’s established interacti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…To confirm that our selection data reflect Rev functional requirements, we assayed individual alanine mutants at the nine NES residues in a p24 Rev-dependent RRE reporter assay (Smith et al, 1990). Mutation of any of the leucines (positions 75, 78, 81, and 83) or proline at position 76 resulted in loss of function (Figure 4A; high p24 = active Rev), consistent with previous data of Crm1 binding residues (Figure 1C) (Fornerod et al, 1997;Güttler et al, 2010;Booth, Cheng and Frankel, 2014;Jayaraman et al, 2019).…”
Section: Functional Assays Confirm the Importance Of Rev Nes Hydrophobic Residues And Llp-2 Charged Residuessupporting
confidence: 89%
See 2 more Smart Citations
“…To confirm that our selection data reflect Rev functional requirements, we assayed individual alanine mutants at the nine NES residues in a p24 Rev-dependent RRE reporter assay (Smith et al, 1990). Mutation of any of the leucines (positions 75, 78, 81, and 83) or proline at position 76 resulted in loss of function (Figure 4A; high p24 = active Rev), consistent with previous data of Crm1 binding residues (Figure 1C) (Fornerod et al, 1997;Güttler et al, 2010;Booth, Cheng and Frankel, 2014;Jayaraman et al, 2019).…”
Section: Functional Assays Confirm the Importance Of Rev Nes Hydrophobic Residues And Llp-2 Charged Residuessupporting
confidence: 89%
“…The present study shows that residues can functionally segregate even when both overlapping segments are structured. We probed residues in the Env gp41 LLP-2 that overlap with the Rev NES and compared the limits to which this domain can tolerate mutation to the already wellestablished mutational limits of Rev (Jayaraman et al, 2019). Interestingly, we observed that critical residues in both proteins are located on one face of a helix such that they was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent mutagenesis research suggests that the CTD may help stabilize Rev and prevent aggregation [173]. Conversely, an increase in HIV-1 fitness is observed when stop codons are included in the CTD, suggesting it may play an inhibitory role [174]. More work must be carried out to resolve the molecular function of the CTD.…”
Section: The Known Unknowns Of the Hiv-1 Rev Proteinmentioning
confidence: 99%
“…75-83) which is recognized in the nucleus by CRM1 in complex with RanGTP. Residues C-terminal to the NES enhance protein stability 77,78 , become partly ordered when Rev forms filaments 67 , and have been predicted to interact with the NTD 79 and to regulate accessibility of the NES 80 . The NTD includes an a-helical hairpin (res.…”
mentioning
confidence: 99%